Retinoschisin gene therapy in photoreceptors, Müller glia, or all retinal cells in the Rs1h−/− mouse - Byrne, Leah C. (2014)
X-linked retinoschisis, a disease characterized by splitting of the retina, is caused by mutations in the retinoschisin gene, which encodes a secreted cell adhesion protein. Currently, there is no effective treatment for retinoschisis, though viral vector-mediated gene replacement therapies offer promise. We used intravitreal delivery of three different AAV vectors to target delivery of the RS1 gene to Müller glia, photoreceptors, or multiple cell types throughout the retina. Müller glia radially span the entire retina, are accessible from the vitreous, and remain intact throughout progression of the disease. However, photoreceptors, not glia, normally secrete retinoschisin. We compared the efficacy of rescue mediated by retinoschisin secretion from these specific subtypes of retinal cells in the Rs1h−/− mouse model of retinoschisis. Our results indicate that all three vectors deliver the RS1 gene, and that several cell types can secrete retinoschisin, leading to transport of the protein across the retina. The greatest long-term rescue was observed when photoreceptors produce retinoschisin. Similar rescue was observed with photoreceptor-specific or generalized expression, though photoreceptor secretion may contribute to rescue in the latter case. These results collectively point to the importance of cell targeting and appropriate vector choice in the success of retinal gene therapies.